The long journey of stem cell therapeutics. - Crawford, Sarah (Genome Medicine, 2012)
A report on the Euroepistem 2011 meeting 'Epigenomic Programming and Stem Cells for Drug Discovery', Paris, France, 21-22 November 2011.
Keywords: Article; dept.bio; embryonic stem cell; epigenetics; gene; gene silencing; human; induced pluripotent stem cell; nonhuman; priority journal; stem cell transplantation; transcription regulation